Дослідження структури множини неперервних розв’язків систем лінійних функціонально-різницевих рівнянь - Пелюх, Г.П.; Сiвак, О.А. (Нелінійні коливання, 2009)
Установлены условия существования непрерывных решений систем линейных функциональноразностных уравнений с линейно преобразованным аргументом и разработан метод их построения. We find conditions for existence of continuous solutions to a system of linear functional-difference equations with linearly transformed argument, and develop a method to construct such solutions.